A stochastic spreadsheet model analysing investment options for the development of pasture on beef cattle farms : a dissertation submitted in partial fulfilment of the requirements for the degree of Master in Applied Science at Massey University - Silva, João Antonio Gomes Martins da (Massey University, 1997)
The decision to proceed with farm development to increase animal production is complex. Standalone personal computer software to study either the financial or physical aspects of farm development is available, but models which integrate these components and account for the risks associated with the investment are not. A stochastic spreadsheet (Microsoft Excel®) model was therefore developed to predict the profitability, feasibility and risk of pasture development for two case farms: one in southern Brazil and the other near Wanganui in New Zealand. Pasture was developed at different rates for each farm and the model was used to predict the associated physical and financial changes over-time and a probability distribution of the net present values (NPV) of the net operating profit after tax and before interest (NOPAT) relative to the status quo situation. The extra pasture was used solely for increasing beef cattle production. On the Brazilian case farm the development of 2,263 ha at two rates was studied. The continuation of the status quo had first degree stochastic dominance in terms of the NPV over both development rates; it was superior by about NZ$ 46.000 for the 200 ha/y option and ca. NZ$ 110.000 for the 500 ha/y option at a 16% discount rate. However, at a 6% discount rate the 500 ha/y development rate had first degree stochastic dominance in terms of the NPV over both the continuation of the status quo (by about NZ$ 960.000) and the 200 ha/y option (ca. NZ$ 120.000). This indicates that pasture development could proceed profitability if interest rates continue to fall in Brazil as predicted. For the New Zealand case farm the development of 247 ha at 50 ha/y had first degree stochastic dominance over the 25 ha/y (ca. NZ$ 24,000) and continuation of the status quo (ca. NZ$ 208.000) at a 6% discount rate. Pasture development should therefore continue. Stochastic analysis of the pasture development investment options gave a better insight into the likely outcomes for a project, and provides the farmer with more information for making a decision on whether, and how. to proceed with farm development. The model could easily be adapted for studying farm development with respect to other types of livestock enterprises Keywords: pastures, development, risk, feasibility, profitability, model.
Keywords: Farm management -- Data processing; Pastures; Economic aspects -- Mathematical models; New Zealand -- Case studies; Brazil -- Case studies